The professionalisation of academic advising practices in South Africa: A competency framework for professional academic advisors (Journal of Student Affairs in Africa, 2026)
Owing to the high attrition rates faced by South African higher education institutions, academic advising has become a crucial strategy for enhancing student success and retention. Institutions committed to improving student learning, persistence and graduation must ensure that academic advisors receive targeted training and professional development. Such initiatives should focus on building competencies tailored to the South African higher education context and its unique challenges. However, existing literature on advising competencies in South Africa remains limited and some still regard the field as being in the early stages of development. This qualitative study aims to propose a competency framework for academic advisors in South Africa, highlighting the knowledge, skills, attitudes, and behaviours associated with professional advising from a developmental perspective. The researcher used the six steps outlined by Dalton to draft a competency framework for advisors at the University of the Free State. Dalton’s steps included a literature review of existing advising frameworks, a job analysis of advisors in various roles, and a qualitative content analysis of the data. As the primary outcome of this competency modelling process, the article presents a contextually relevant competency framework for academic advisors at a South African institution.
Keywords: academic advising; competency modelling; Industrial Psychology; South Africa; professional advisors; professional development; training and development